If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -4) + -2(x + -8) = 4(x + -9) + 6 Reorder the terms: 7(-4 + x) + -2(x + -8) = 4(x + -9) + 6 (-4 * 7 + x * 7) + -2(x + -8) = 4(x + -9) + 6 (-28 + 7x) + -2(x + -8) = 4(x + -9) + 6 Reorder the terms: -28 + 7x + -2(-8 + x) = 4(x + -9) + 6 -28 + 7x + (-8 * -2 + x * -2) = 4(x + -9) + 6 -28 + 7x + (16 + -2x) = 4(x + -9) + 6 Reorder the terms: -28 + 16 + 7x + -2x = 4(x + -9) + 6 Combine like terms: -28 + 16 = -12 -12 + 7x + -2x = 4(x + -9) + 6 Combine like terms: 7x + -2x = 5x -12 + 5x = 4(x + -9) + 6 Reorder the terms: -12 + 5x = 4(-9 + x) + 6 -12 + 5x = (-9 * 4 + x * 4) + 6 -12 + 5x = (-36 + 4x) + 6 Reorder the terms: -12 + 5x = -36 + 6 + 4x Combine like terms: -36 + 6 = -30 -12 + 5x = -30 + 4x Solving -12 + 5x = -30 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 5x + -4x = -30 + 4x + -4x Combine like terms: 5x + -4x = 1x -12 + 1x = -30 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 1x = -30 + 0 -12 + 1x = -30 Add '12' to each side of the equation. -12 + 12 + 1x = -30 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -30 + 12 1x = -30 + 12 Combine like terms: -30 + 12 = -18 1x = -18 Divide each side by '1'. x = -18 Simplifying x = -18
| 6x-4y+5z=27 | | -10x-21=-12x+31 | | 8x+4y+7z-4x+4z-5y= | | n+3.4=8.3 | | 4y-6(y+8)=8y+12 | | 7x^2-10*x-5=0 | | -5+6j=-53 | | -1x+3=19 | | 39=-3+5(x+6) | | 7w+8=64 | | 2x-5=-(3x+7) | | 3=-6x+3(x+3) | | 19-3x=9x-5 | | 1.8+7n=4n | | y+6=5x+3xr-4 | | 9-3p=3 | | 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y |